Minimally Invasive Surgical Treatment of Pilonidal Disease: Mid-Term Retrospective Analysis of a Single Center - Oliveira, Ana Isabel; Barroso, Catarina; Osório, Angélica; Correia-Pinto, Jorge (Frontiers in Pediatrics, 2019)
Background: Sacrococcygeal Pilonidal Disease (PD) is commonly treated with excision and primary closure techniques (EPC). Minimally invasive techniques (MIT), such as EPSiT and Pit-picking, had been recently advocated promising better outcomes. We analyzed mid-term results from our center after introduction of MIT to treat PD. Methods: Patients submitted to MIT (n=44) with a median follow-up of 37 months were analyzed and compared with patients submitted to EPC (n=70) with a median follow-up of 5 years. Both groups included patients operated in our department between 2011-2016 and have similar demographic and clinical characteristics. We compared operative time and post-operative parameters such as time with pain, dressing time and time to relapse. Results: The post-operative time with pain was significantly lower, whereas the dressing time was significantly longer, in MIT when compared to the EPC group. The relapse rate was similar in both groups but the follow-up is shorter in the MIT group. In addition, the analysis of patients free of disease using Kaplan-Meier curves revealed that relapse tends to occur more precociously in MIT than in EPC patients (p=0.014). Interestingly, in the subgroup of patients with previous surgery, MIT’s relapse rate was significantly lower than in the EPC group (30 vs. 100%, p<0.001). Conclusions: MIT has the advantage of having a shorter time with pain in the postoperative period, while EPC benefits from a shorter dressing time. In general, the relapse of the disease tends to manifest more precociously in MIT patients. Moreover, in the subgroup of patients with previous surgery, MIT seems to have significantly better results when compared to EPC.